Economic evaluations of palliative care models: A systematic review. (January 2020) - Mathew, Christine; Hsu, Amy T.; Prentice, Michelle; Lawlor, Peter; Kyeremanteng, Kwadwo; Tanuseputro, Peter; Welch, Vivian
Background: Palliative care aims to improve quality of life by relieving physical, emotional, and spiritual suffering. Health system planning can be informed by evaluating cost and effectiveness of health care delivery, including palliative care. Aim: The objectives of this article were to describe and critically appraise economic evaluations of palliative care models and to identify cost-effective models in improving patient-centered outcomes. Design: We conducted a systematic review and registered our protocol in PROSPERO (CRD42016053973). Data sources: A systematic search of nine medical and economic databases was conducted and extended with reference scanning and gray literature. Methodological quality was assessed using the Drummond checklist. Results: We identified 12, 632 articles and 5 were included. We included two modeling studies from the United States and England, and three economic evaluations from England, Australia, and Italy. Two studies compared home-based palliative care models to usual care, and one compared home-based palliative care to no care. Effectiveness outcomes included hospital readmission prevented, days at home, and palliative care symptom severity. All studies concluded that palliative care was cost-effective compared to usual care. The methodological quality was good overall, but three out of five studies were based on small sample sizes. Conclusion: Applicability and generalizability of evidence is uncertain due to small sample sizes, short duration, and limited modeling of costs and effects. Further economic evaluations with larger sample sizes are needed, inclusive of the diversity and complexity of palliative care populations and using patient-centered outcomes.